DIGITAL PAYMENTS AND FINTECH INNOVATION: TRANSFORMING THE FINANCIAL ECOSYSTEM - Shruti; Priyanka; Prasad; Vinayak (International Educational Journal of Science and Engineering, 2026)
The rapid evolution of Financial Technology (FinTech) has significantly transformed the global financial ecosystem, particularly through the expansion of digital payment systems. With the integration of technologies such as mobile banking, blockchain, artificial intelligence, and cloud computing, financial services have become more accessible, efficient, and customer-centric. This paper examines the role of digital payments in driving financial inclusion, enhancing transaction efficiency, and reshaping traditional banking systems. It also explores key technologies, challenges, and future trends in FinTech innovation. The study finds that FinTech-driven digital payments improve transparency, reduce transaction costs, and support economic growth, while also raising concerns related to cybersecurity, regulation, and data privacy.